DIVERSIDADE DE PEIXES DE ÁGUA DOCE DO PARQUE NACIONAL DOS LENÇÓIS MARANHENSES. - FERREIRA, Beldo Rywllon Abreu (2018)
Conservation units (CU) correspond to one of the alternatives for the protection of habitats and preservation of the natural genetic heritage. Many of these areas safeguard important bodies of water. The National Park (PARNA) of Lençóis Maranhenses, managed by the federal government, is characterized by the occurrence of dunes and lagoons, conferring a great scenic attraction. However, even though it is an important area of protection, 22 years after its creation, there is still scarce knowledge about the biodiversity and the threats that exist in this CU. One of the knowledge gaps is related to ichthyofauna. Since the elaboration of its Management Plan, more than 15 years ago, there is no updated reference on the diversity of fish species in the different aquatic environments that can be found in and around the Park. Despite being an integral protection area, the environments contained in the Lençóis Maranhense PARNA have been under great pressure, especially those related to tourism and colonization, which is growing in this region. Thus, the objective of the present study is to carry out an inventory of freshwater fish in the Lençóis Maranhenses National Park. Most of the material available for study comes from the Fish Collection of the Federal University of Maranhão (CPUFMA), covering 20 sites distributed within and outside the limits of the Lençóis Maranhenses PARNA. The CPUFMA material, obtained in two campaigns in the year 2000, was complemented by a third expedition, held in June 2017. 46 species of freshwater fish were listed for the coastal drainage of the Preguiças and Periá basins belonging to 24 families and 10 orders. The orders Characiformes and Cichliformes were the most representative. At least six species known to be endemic to the Parnaíba region occur in the Park, demonstrating the importance of conservation units for the maintenance of endangered fauna. The record of endemic species, associated with possible new species, becomes important for the area, since its occurrence can be used as a subsidy in the definition of conservation strategies for the area.